Hello!

Multiply the first equation by 2 and the second by (-3) and add them:

2*(6x+7y) = 2*(-6), or 12x+14y = -12

and

(-3)*(4x+5y) = (-3)*(-6), or -12x-15y = 18.

After addition we have

-15y + 14y = -y = 18-12 = 6, or y=-6.

Then recall 4x+5y=-6, or 4x+5*(-6) = -6, 4x = 5*6-6 = 4*6, so x = 6.

The answer: x=6, y=-6.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up